(untitled) (Modern Problems of Metallurgy, 2019)
The composition of spent pickling solutions depends on many factors: the initial composition of the solutions, the type of scale, the specific surface of the products, the method of etching, etc. But there are some utilization features associated with the presence of organic substances, inhibitors, low pH values, interchangeable concentrations of iron salts (50-500 g / dm3), the presence of insoluble impurities. Liquid wastes from pickling and electroplating departments accumulate, and the raw material base of industry is rapidly depleting. Therefore, the processing of such waste will help solve a number of issues, including the production of a cheaper domestic product that can compete on the world market with other manufacturers. The article discusses the existing methods of disposal of waste pickling solutions. The influence of the main factors on the formation of mineralized oxygene pigments was studied. With the help of X-ray and microscopic analyzes, areas of formation of a yellow mineralized oxide pigment are shown.